The Effect of Salicylic Acid and 20 Substituted Molecules on Alleviating Metolachlor Herbicide Injury in Rice (Oryza sativa) - Xile Deng; Wenna Zheng; Xiaomao Zhou; Lianyang Bai (Agronomy, 2020)
Salicylic acid (SA) is an endogenous plant hormone that has a wide range of pharmacological effects. Studies have indicated that SA has herbicide safening activity. In this study, the herbicide safening activity of SA and 20 substituted molecules were tested on agar-cultured rice. Biological assay results indicated that SA and substituted SA had a low inhibitory effect on the growth of rice seedlings (Oryza sativa), and partially alleviated the effects of metolachlor toxicity. Moreover, at 0.25 mg L−1, the safening effect of compounds l and u lessened the effects of metolachlor phytotoxicity on plant height and fresh weight when compared to the effects of the control, fenclorim. The effects of metolachlor toxicity were reduced on root length due to the safening effects of compounds l, n, and u; these effects were greater than those of fenclorim. These compounds could facilitate the development of novel herbicide safeners.